Search for resonant and nonresonant production of pairs of dijet resonances in proton-proton collisions at s $$ \sqrt{s} $$ = 13 TeV - The CMS collaboration; A. Tumasyan; W. Adam; J. W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; A. Escalante Del Valle; P. S. Hussain; M. Jeitler; N. Krammer; et al. (Journal of High Energy Physics, 2023)
Abstract A search for pairs of dijet resonances with the same mass is conducted in final states with at least four jets. Results are presented separately for the case where the four jet production proceeds via an intermediate resonant state and for nonresonant production. The search uses a data sample corresponding to an integrated luminosity of 138 fb −1 collected by the CMS detector in proton-proton collisions at s $$ \sqrt{s} $$ = 13 TeV. Model-independent limits, at 95% confidence level, are reported on the production cross section of four-jet and dijet resonances. These first LHC limits on resonant pair production of dijet resonances via high mass intermediate states are applied to a signal model of diquarks that decay into pairs of vector-like quarks, excluding diquark masses below 7.6 TeV for a particular model scenario. There are two events in the tails of the distributions, each with a four-jet mass of 8 TeV and an average dijet mass of 2 TeV, resulting in local and global significances of 3.9 and 1.6 standard deviations, respectively, if interpreted as a signal. The nonresonant search excludes pair production of top squarks with masses between 0.50 TeV to 0.77 TeV, with the exception of a small interval between 0.52 and 0.58 TeV, for supersymmetric R-parity-violating decays to quark pairs, significantly extending previous limits. Here, the most significant excess above the predicted background occurs at an average dijet mass of 0.95 TeV, for which the local and global significances are 3.6 and 2.5 standard deviations, respectively.